Eksistensi Peraturan Menteri Agama (PMA) Nomor 10 Tahun 2020 Sebagai Penguatan Pendidikan Keagamaan Hindu Di Indonesia - I Made Bagus Andi Purnomo; Ni Made Indiani (Purwadita : Jurnal Agama dan Budaya, 2021)
The presence of PMA 10/2020 was also very well received by pasraman managers in regions throughout Indonesia. Moreover, there are several articles that explain the opportunity for the conversion of formal pasraman or widya pasraman after the entry into force of PMA 56/2014. This research is classified as a qualitative descriptive study. The results of this study are that there are several points of change from PMA 56/2014 to PMA 10/2020. Some of them, such as the clause on the establishment of a pasraman which is more mature, changes in the curriculum in religious aspects, guidelines for diplomas and also the understanding of widya pasraman. The implementation of Widya Pasraman is generally welcomed. However, several things need to be matured and socialized more massively, mainly related to changes to a more technical and holistic curriculum. Regarding the conversion clause, it is highly appreciated by various groups. The impact of PMA 10/2020 on the existence of pasraman is on the administrative and sociological impact.